2022
DOI: 10.1542/peds.2021-054939
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Tax Credits on Rates of Child Maltreatment Reports in the United States

Abstract: OBJECTIVES: Poverty and low income are associated with increased risk for child maltreatment. The Earned Income Tax Credit (EITC) and Child Tax Credit (CTC) are among the largest antipoverty programs in the United States. We estimated associations between income transfer payments via the EITC and CTC and child maltreatment reports in the period shortly after families receive payments from these programs. METHODS: We linked we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…First, rigorously studying the effect of income support policies on CAN is challenging owing to difficulties with randomizing income supports. Several previous studies [3][4][5][6][7][8]28,30 have used approaches that rely on changes in public assistance programs.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, rigorously studying the effect of income support policies on CAN is challenging owing to difficulties with randomizing income supports. Several previous studies [3][4][5][6][7][8]28,30 have used approaches that rely on changes in public assistance programs.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%
“…For example, a more generous Earned Income Tax Credit (EITC) and higher minimum wages have been shown to reduce child maltreatment and foster care entry. [3][4][5][6][7][8] However, these studies are unable to separately estimate the effects of income and those of employment-related decisions, such as whether, how much, and when to work. These employment decisions can also affect child maltreatment, which can confound the estimated effects of income support.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we would expect reports of child maltreatment to dramatically increase as schools returned to in-person learning and children had more frequent contact with mandatory reporters. Based upon the recent findings of Kovski and colleagues (2022) regarding immediate decreases in child maltreatment reports following the distribution of EITC and CTC payments, we would also expect to see a declining trend in child maltreatment following the distribution of expanded CTC payments during COVID-19. A more nuanced examination of maltreatment rates during the span of the COVID-19 pandemic will help us understand what factors may have protected families or placed them at greater risk.3.…”
mentioning
confidence: 94%
“…There is growing evidence that economic and concrete supports reduce child abuse and neglect (Maguire-Jack et al, 2021). In fact, a more recent paper using data from prior to COVID-19 showed that in the weeks following child tax credit distributions, reports of child maltreatment decreased (Kovski et al, 2022). We have every reason to believe based on prior research evidence that the mechanisms driving these decreases were also evident during the pandemic; unfortunately, we do not have the empirical data yet to declare that to be the case.…”
mentioning
confidence: 99%
“…Furthermore, policy level initiatives aimed at supporting low income families have the potential to reduce the rates of child abuse and maltreatment, highlighting how SES may be an upstream target amenable to intervention. For example, for every $1000 increase per child in the Earned Income Tax Credit (EITC) and Child Tax Credit, state level rates of reported maltreatment decreased by an estimated 5% [ 35 ••]. Refundable EITCs were responsible for an estimated 13% reduction in abusive head trauma admissions in children younger than 2 years of age [ 36 ].…”
Section: Introductionmentioning
confidence: 99%